SEMI-ANALYTUCAL SOLUTION TO DYNAMIC ANALYSIS FOR PLOUGH SYSTEM - CHEN Hong Yue; ZHANG Kun; ZHANG Yu; MAO Jun; SONG Qiu Shuang (Jixie qiangdu)
According to working features of plough system,three sections of visco-elastic dynamic model were established based on wave theory. The boundary conditions,joining conditions and initial condition of wave equation under stable running were determined. Dynamic model of plough system including three partial differential equations were solved with separation variables method. The dynamic displacement, velocity, and tension of plough system under stable running were obtained. The tension change of plow systems at different locations were analyzed. The results show that the tension change of plow systems at different locations increase with cutting depth,and the cutting speed has little influence on tension. Compared with the experimental results,the distribution law of characteristics is uniform, and deviation meets accuracy requirements,Feasibility and correctness of the suggested method is verified.